Erwinia chrysanthemi in Israel - epidemiology and monitoring in seed tubers - Tsror (Lahkim), Leah; Erlich, Orly; Lebiush, S.; Haar, Jan J. van de (MTT, 2007)
In recent years, Erwinia chrysanthemi (Ech) on potato in Israel, in plants grown from imported Dutch seed tubers has been occurring more frequently causing economic damage. Disease symptoms first appear as wilt of the top leaves, which then spreads to the lower ones, followed by desiccation. Discoloration of the vascular system in the stem base is usually observed, followed by external darkening. In severe infections, the stem, and even the whole plant can dry out. Symptoms are usually associated with soft rot of the mother tuber, and sometimes (depending on level of infection) of the daughter tubers as well. The objectives of the present study were: a) to assess the impact of Ech-infected seed tubers imported from The Netherlands on disease expression in Israel, b) to develop a protocol for the detection of latent Ech infection in seed tubers. In spring 2004, disease was observed in several plots on imported cvs. Desirée and Mondial. In 2005, disease incidence on various imported cultivars ranged from 5 to 30% (8.2% on average) on more than 200 ha. In the autumn crop where domestic tubers harvested from an infested field were used disease incidence was 10-15%. In 2006, the disease was observed on more than 260 ha in various cultivars with disease incidence ranging from 2 to 30% (10% on average). Seed tubers sampled from commercial lots imported from Holland were tested for latent Ech infection, based on bio-PCR or enrichment ELISA. Out of 36 tested lots 24 were Ech-positive. Disease levels recorded in the fields in these lots ranged from 3% to 35% (10% on average), with only one exceptional case, where a low incidence of diseased plants was observed in a field originated from a Ech-negative seed lot. A protocol for detection of Ech in seed tubers was developed. A sample comprised of 200 tubers per 25 tons per lot divide into four or 10 replicates (50/20 tubers each), surfacesterilize with 0.5% NaOCl for 1 min, and the stolon end of each tuber was cut and placed in enrichment medium. After incubation of 48h, 0.2-ml aliquot was used for ELISA analysis or DNA extracted from the supernatant was used for PCR analysis. Our findings so far demonstrated the higher sensitivity of the bio PCR in comparison with the ELISA. This protocol is being tested also in spring 2007 with a large number of seed lots. Samples from these lots were planted in the field and Ech incidence is being recorded. Correlations between latent infections in the seed tubers and disease expression will be further studied, in order to evaluate the accuracy of the suggested protocol, and/or to improve it.
Keywords: Ka; Erwinia chrysanthemi; latent infection teting; bio PCR; enrichment ELISA